2018
DOI: 10.4103/jlp.jlp_67_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal function in subclinical hypothyroidism

Abstract: INTRODUCTION:Patients with subclinical hypothyroidism (SCH) have a few or no symptoms or signs of thyroid dysfunction and thus by its very nature, SCH is a laboratory diagnosis. Serum creatinine is elevated and glomerular filtration rate (GFR) values are reversibly reduced in overt hypothyroid patients. We hypothesize that SCH also may be associated with low GFR.AIMS AND OBJECTIVES:The objective of this study was (1) to know the effect of SCH on kidney function, (2) to find the correlation between the renal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
3
15
0
1
Order By: Relevance
“…Levels of the circulating thyroid hormones T3 and T4 were measured in another cohort ( N = 3 vehicle, N = 5 sunitinib) of mice with no significant differences found between groups data not shown). These findings suggest presence of sub‐clinical hypothyroidism, which has been previously been linked to poor glomerular filtration rates …”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Levels of the circulating thyroid hormones T3 and T4 were measured in another cohort ( N = 3 vehicle, N = 5 sunitinib) of mice with no significant differences found between groups data not shown). These findings suggest presence of sub‐clinical hypothyroidism, which has been previously been linked to poor glomerular filtration rates …”
Section: Resultsmentioning
confidence: 53%
“…Sunitinib treatment resulted in human equivalent grade 2 proteinuria (30–100 mg dL −1 of protein in the urine; 1–2 g per day). The effect of sunitinib on thyroid morphology and function was also assessed to investigate preclinical evidence of clinically reported thyroid AEs . A significant decrease in thyroid epithelial cell height in the thyroids of mice ( N = 3 per group) treated with 40 mg kg −1 sunitinib was observed (Figure C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothyroid Cases r value p value eGFR(ml/min) vs T 3 Hypothyroidism is a common endocrine disorder associated with decreased myocardial contractility, cardiac output and increase in peripheral vascular resistance. The increase in peripheral resistance can predispose to the alteration in renal hemodynamics such as reduced renal blood flow and diminution of glomerular filtration rate resulting in decrease in the clearance of certain substances like creatine kinase, creatinine and others in hypothyroidism [9]. Hypothyroidism may be contributing to the low GFR in some of the hypothyroid cases [10].…”
Section: Pairmentioning
confidence: 99%
“…Hypothyroidism diminishes protein synthesis and cellular development, which leads to decreases in cell number, density, and size of the kidney [3]. It has been demonstrated that subclinical hypothyroidism might be a risk factor for faster decline of renal function [4][5][6], with possible effect on recovery or preservation of renal function with treatment [7,8]. However, this finding are controversial and the effect of low free thyroxine (LFT) levels on eGFR decline in CKD patients has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%